New species and records of Anacroneuria (Plecoptera: Perlidae) from Ecuador and Paraguay - Stark, Bill P. (Illiesia, 2012)
Five new species of Anacroneuria Klapálek are described from Ecuadorian specimens. New taxa include A. apuela, A. cushueme, A. kayceae, A. malkini, and A. pichincha. New distribution records are also presented for six species including three, A. atrifrons Klapálek, A. chavin Stark & Sivec and A. guambiana Zúniga & Stark, not previously reported from Ecuador. An additional species represented by a female specimen is described under an informal designation, the larva of A. gaumbiana is described, and a checklist of 54 species reported for Ecuador is presented. The first Paraguayan specimens of A. atrifrons are also reported.
Keywords: Anacroneuria; entomology; Perlidae; Plecoptera; new species; Ecuador; Paraguay